CIRBP mRNA level in breast cancer is associated with HIF1α gene expression and microvascular density - Sajad Monjezi; Vahid Soleimani; Maryam Cheraghzadeh; Saeed Ghanbari; Maryam Adelipour (BMC Research Notes)
Abstract Objective Based on the available evidence, the cold-inducible RNA-binding protein (CIRBP) appears to play a role in increasing the stability of hypoxia-inducible factor 1-alpha (HIF1α) mRNA. This research aimed to examine the levels of CIRBP and HIF1α mRNA within breast tumor tissues and explore the relationship between their gene expression and tumor Microvascular density (MVD). Results The results revealed a significant upregulation of CIRBP (5.07-fold) and HIF1α (4.5-fold) gene expression in BC samples compared to the surrounding normal tissues (p < 0.001). This upregulation was also associated with various clinicopathologic features. Furthermore, there was a correlation between CIRBP mRNA expression, HIF1α mRNA expression, and MVD. Consequently, this study suggests that CIRBP may have a role in promoting angiogenesis in BC.